2022
DOI: 10.1007/s12094-022-02998-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual neoadjuvant blockade plus chemotherapy versus monotherapy for the treatment of women with non-metastatic HER2-positive breast cancer: a systematic review and meta-analysis

Abstract: Dual neoadjuvant blockade plus chemotherapy versus monotherapy for the treatment of women with non-metastatic HER2-positive breast cancer: a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
1
0
0
Order By: Relevance
“…However, approximately half of the patients in our series achieved a pCR without receiving pertuzumab. This finding further confirmed that a sizeable proportion of them could obtain an excellent outcome from neoadjuvant treatment with trastuzumab and taxane-based chemotherapy alone ( 35 ). Further research on predictive biomarkers is warranted to identify subgroups of patients who might benefit most from the addition of pertuzumab to standard NACT ( 36 ).…”
Section: Discussionsupporting
confidence: 70%
“…However, approximately half of the patients in our series achieved a pCR without receiving pertuzumab. This finding further confirmed that a sizeable proportion of them could obtain an excellent outcome from neoadjuvant treatment with trastuzumab and taxane-based chemotherapy alone ( 35 ). Further research on predictive biomarkers is warranted to identify subgroups of patients who might benefit most from the addition of pertuzumab to standard NACT ( 36 ).…”
Section: Discussionsupporting
confidence: 70%